2018
DOI: 10.1108/ijppm-06-2017-0149
|View full text |Cite
|
Sign up to set email alerts
|

An investigation into manufacturing performance achievements accrued by Indian manufacturing organization through strategic 5S practices

Abstract: Purpose The purpose of this paper is to evaluate the quantitative and qualitative benefits accrued by an Indian automotive parts industry through strategic 5S implementation initiatives. Design/methodology/approach The study involves evaluation of steps involved in systematic implementation of 5S program methodology in an automotive manufacturing organization and investigation of achievements accrued by the industry through the successful implementation of 5S program. Findings The empirical results of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 30 publications
1
20
0
5
Order By: Relevance
“…The inability to correctly perform tasks, for example due to the lack of appropriate tools or lack of commitment may be due to poor working conditions. Moreover, the 5S system will bring the desired results when all the above-mentioned factors are carried out reliably., what is similar results of another research as [9,10].…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The inability to correctly perform tasks, for example due to the lack of appropriate tools or lack of commitment may be due to poor working conditions. Moreover, the 5S system will bring the desired results when all the above-mentioned factors are carried out reliably., what is similar results of another research as [9,10].…”
Section: Resultssupporting
confidence: 91%
“…The application consists of 5 steps, whose names in Japanese begin with the letter "s", 1S-Selection (Seiri), 2S-Systematyka (Seiton) -3S-Cleaning -4S-Standardization, 5S-Self-discipline. 5S is valuable for enhancing the workplace, as well as that, 5S framework facilitates process and item quality guidelines, decrease lead time, and furthermore, obviously, lessen working expenses and improve overall performance [8] From literaturę perspective several studies have been reported by the practitioners about beneficial impacts of 5S practice in the different enterprises [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Randhawa and Ahuja (2018). “An investigation into manufacturing performance achievements accrued by Indian manufacturing organization through strategic 5S practices,” Int.…”
Section: The Systematic Literature Review (Slr) and Its Findingsmentioning
confidence: 99%
“…Savings were claimed due to lowered usage of a variety of resources. Examples include less employee time (e.g., fewer materials handlers and elimination of weekend cycle counting (Mistry, 2005a, 2005b), less overtime (Billesbach, 1994), shorter process time via better tooling (Deb et al, 2010), fewer production workers (Billesbach, 1994; Conti, 1996), and fewer hours lost to safety incidents and associated lower insurance premiums (Karuppan et al, 1996)); lowered inventory levels and associated holding costs (e.g., Billesbach, 1994; Kaplinsky, 1994); less need for facility space (e.g., due to less inventory on factory floor or in stock rooms [Kaplinsky, 1994; Mistry, 2005a, 2005b]), reduced use of material and labor (e.g., by reducing scrap and rework (Carmignani, 2017; Hung et al, 2011; Murugaiah et al, 2010; Orbak, 2012; Thomas et al, 2009), use of less or cheaper materials (Deb et al, 2010; Krovvidi et al, 2019; Randhawa & Ahuja, 2018) or by more exact filling of packages (Baia, 2015), less use of water (Kaushik & Khanduja, 2009; Pinto Jr. & Mendes, 2017), less energy consumption (Pinto Jr. & Mendes, 2017; Thomas et al, 2009), and lower production costs by rebalancing workers on machines (Kovács, 2020; Sarkar et al, 2015).…”
Section: The Systematic Literature Review (Slr) and Its Findingsmentioning
confidence: 99%
“…To this end, a survey was carried out on a sample of 24 Slovenian companies that operate in the international automotive However, the development of systems for ensuring the reliability of warehousing processes began in the mid-1950s in Japan. The 5S methodology was first implemented in manufacturing under the Toyota Production System [21]. The main benefits of the 5S method are: a cleaner, tidier and more orderly work environment, safer working conditions, reduction of non-value-adding activities, better quality and higher productivity, fewer defects and better availability of equipment, as well as fewer equipment and tools needed [22].…”
Section: Literature Reviewmentioning
confidence: 99%